HEV-associated dendritic cells are observed in metastatic tumor-draining lymph nodes of cutaneous melanoma patients with longer distant metastasis-free survival after adjuvant immunotherapy - Bravo, Alicia Inés; Aris, Mariana; Panouillot, Marylou; Porto, Martina; Dieu-Nosjean, Marie-Caroline; Teillaud, Jean-Luc; Barrio, María Marcela; Mordoh, José (Frontiers in Immunology, 2023)
Introduction Tissue biomarkers that aid in identifying cutaneous melanoma (CM) patients who will benefit from adjuvant immunotherapy are of crucial interest. Metastatic tumor-draining lymph nodes (mTDLN) are the first encounter site between the metastatic CM cells and an organized immune structure. Therefore, their study may reveal mechanisms that could influence patients´ outcomes. Methods Twenty-nine stage-III CM patients enrolled in clinical trials to study the vaccine VACCIMEL were included in this retrospective study. After radical mTDLN dissection, patients were treated with VACCIMEL (n=22) or IFNα-2b (n=6), unless rapid progression (n=1). Distant Metastasis-Free Survival (DMFS) was selected as an end-point. Two cohorts of patients were selected: one with a good outcome (GO) (n=17; median DMFS 130.0 months), and another with a bad outcome (BO) (n=12; median DMFS 8.5 months). We analyzed by immunohistochemistry and immunofluorescence the expression of relevant biomarkers to tumor-cell biology and immune cells and structures in mTDLN, both in the tumor and peritumoral areas. Results In BO patients, highly replicating Ki-67+ tumor cells, low tumor HLA-I expression and abundant FoxP3+ lymphocytes were found (p=0.037; p=0.056 and p=0.021). In GO patients, the most favorable biomarkers for prolonged DMFS were the abundance of peri- and intra-tumoral CD11c+ cells (p=0.0002 and p=0.001), peri-tumoral DC-LAMP+ dendritic cells (DCs) (p=0.001), and PNAd+ High Endothelial Venules (HEVs) (p=0.004). Most strikingly, we describe in GO patients a peculiar, heterogeneous structure that we named FAPS (Favoring Antigen-Presenting Structure), a triad composed of DC, HEV and CD62L+ naïve lymphocytes, whose postulated role would be to favor tumor antigen (Ag) priming of incoming naïve lymphocytes. We also found in GO patients a preferential tumor infiltration of CD8+ and CD20+ lymphocytes (p=0.004 and p=0.027), as well as peritumoral CD20+ aggregates, with no CD21+ follicular dendritic cells detected (p=0.023). Heterogeneous infiltration with CD64+CD68-CD163-, CD64+CD68+CD163- and CD64+CD68+CD163+ macrophages were observed in both cohorts. Discussion The analysis of mTDLN in GO and BO patients revealed marked differences. This work highlights the importance of analyzing resected mTDLN from CM patients and suggests a correlation between tumor and immune characteristics that may be associated with a spontaneous or vaccine-induced long DMFS. These results should be confirmed in prospective studies.